2015
DOI: 10.1002/cm.21239
|View full text |Cite
|
Sign up to set email alerts
|

Palladin expression is a conserved characteristic of the desmoplastic tumor microenvironment and contributes to altered gene expression

Abstract: The stroma surrounding solid tumors contributes in complex ways to tumor progression. Cancer-associated fibroblasts (CAFs) are the predominant cell type in the tumor stroma. Previous studies have shown that the actin-binding protein palladin is highly expressed in the stroma of pancreas tumors, but the interpretation of these results is complicated by the fact that palladin exists as multiple isoforms. In the current study, the expression and localization of palladin isoform 4 was examined in normal specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Some have been established, but a true, unique marker is yet to be discovered. Native fibroblasts stain for vimentin and, once activated, stain positive for alpha-smooth muscle actin (αSMA) [31]. Other CAF markers previously reported include stromal cell-derived factor-1α (SDF1A), fibroblast activation protein (FAP), and fibroblast-specific protein-1 (FSP-1) [28, 32].…”
Section: Cellular Markers For Cafsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have been established, but a true, unique marker is yet to be discovered. Native fibroblasts stain for vimentin and, once activated, stain positive for alpha-smooth muscle actin (αSMA) [31]. Other CAF markers previously reported include stromal cell-derived factor-1α (SDF1A), fibroblast activation protein (FAP), and fibroblast-specific protein-1 (FSP-1) [28, 32].…”
Section: Cellular Markers For Cafsmentioning
confidence: 99%
“…More recent studies, such as that by Cannon et al, found that palladin, an actin-binding protein highly expressed in cancers, actually precedes αSMA expression in cells undergoing activation to CAFs. The group further elucidated the role of palladin isoform 4 in CAF activation including its location in the cytoplasm and nucleus, and its role in expression of genes associated with collagen formation and MMP activation pathways demonstrated by shRNA knockdown [31]. …”
Section: Cellular Markers For Cafsmentioning
confidence: 99%
“…NG2 and PDGFR‐β are also expressed in normal pericytes, and podoplanin is expressed in lymphatic endothelial cells . Furthermore, Cannon et al found that paladin, a highly expressed actin binding protein in cancer, was expressed earlier than α‐SMA when activated in CAFs . Cytokeratin and CD31 are regarded as negative markers because CAFs had no epithelial or endothelial characteristics .…”
Section: Sources and Markers Of Cancer‐associated Fibroblastsmentioning
confidence: 99%
“…38 Furthermore, Cannon et al found that paladin, a highly expressed actin binding protein in cancer, was expressed earlier than α-SMA when activated in CAFs. 39 Cytokeratin and CD31 are regarded as negative markers because CAFs had no epithelial or endothelial characteristics. 37,40 Because of the lack of specific CAF markers, combinations of markers may help identify CAFs.…”
Section: Source S and Mark Er S Of C An Cer-a Sso Ciated Fib Rob L mentioning
confidence: 99%
“…22,[29][30][31] Palladin is expressed in myofibroblasts of the stroma of solid tumors, and it is thought to promote the migration of these cells and thereby to facilitate tumor cell invasion. 32,33 Indeed, palladin may serve as a marker for cancer-associated myofibroblasts. 34 These observations suggest that palladin might also play an important role in corneal myofibroblasts, in which actin stress fibers have been shown to be abundant both in vitro and in vivo.…”
mentioning
confidence: 99%